(untitled) (Journal of Bio-Science, 2021)
Meiotic behavior of ten pteridophyte species from Bangladesh was analyzed in the present investigation. In SMCs of Adiantum capillus-veneris, thirty distinct bivalents were enumerated. In A. caudatum 16 SMCs resulting 64 spores were observed in sporangium which appeared to be diploid sexual. A. lunulatum was found to be triploid apogamous and as diploid sexual forms, thus this species of Adiantum exhibited wide range of morphological variations. Pteris biaurita, P. graffithi and P. vittata were recorded to be n = 29 as diploid. In thelypterids, all the four species were observed to be diploid sexual except C. dentata when it was tetraploid (n = 36, 4x = 144). In C. arida, meiosis was almost regular with 2n = 72 chromosomes. C. cylindrothrix and Ampelopteris prolifera were also found to be diploid sexual, with 2n = 72 chromosomes. J. Bio-Sci. 29(1): 135-142, 2021 (June)